PENERAPAN METODE DISKUSI KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS VIII-1 SMP NEGERI 1 PATUMBAK - Munder Siahaan (JS (JURNAL SEKOLAH), 2019)
Abstract: Application of Group Discussion Methods to Improve Student Learning Outcomes in Mathematics Subjects in Class VIII-1 SMP Negeri 1 Patumbak. This type of research is Classroom Action Research. The research subjects were students of class VIII of SMP Negeri 1 Patumbak T.A 2018/2019, amounting to 34 students. Based on the initial tests conducted, the percentage of students' initial mastery levels was 12 students (64.71%) while 22 students (35.29%) were incomplete. From the results of the study, classical learning completeness has been achieved and there is an increase in learning outcomes in the first cycle (66.72%) and in the second cycle the average grade of the class (77.12%). From the actions and results of the analysis of cycle I and cycle II it can be concluded that the application of the group discussion method can improve student learning outcomes and activeness in mathematics.Keywords: Group Discussion, learning outcomesAbstrak: Penerapan Metode Diskusi Kelompok Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Di Kelas VIII-1 SMP Negeri 1 Patumbak. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Subjek penelitian adalah siswa kelas VIII SMP Negeri 1 Patumbak T.A 2018/2019 yang berjumlah 34 siswa. Berdasarkan tes awal yang dilakukan, persentase tingkat ketuntasan awal siswa adalah sebanyak 12 siswa (64,71%) sedangkan 22 siswa (35,29%) tidak tuntas. Dari hasil penelitian telah tercapai ketuntasan belajar secara klasikal dan ada peningkatan hasil belajar yaitu pada siklus I ( 66,72%) dan pada siklus II nilai rata-rata kelas ( 77,12%). Dari tindakan dan hasil analisis siklus I dan siklus II tersebut dapat disimpulkan bahwa Penerapan metode diskusi kelompok dapat meningkatkan hasil belajar dan keaktifan siswa pada pelajaran matematika.Kata Kunci : diskusi Kelompok, hasil belajar